Enhancement of Growth and Yield of Basil (Ocimum sanctum L.) Plants Using Fermented Goat Manure Fertilizer: Peningkatan Petumbuhan Dan Hasil Tanaman Kemangi (Ocimum Sanctum L.) dengan Pupuk Kandang Kambing Fermentasi - Andriani Eko Prihatiningrum; M Abror; Saiful Arifin (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the influence of fermented goat manure fertilizer on the growth and yield of Holy Basil (Ocimum sanctum L.). A randomized complete block design with three treatments, including no fertilizer, goat manure fertilizer, and fermented goat manure fertilizer, was employed. Variables observed included plant height, leaf count, leaf area, and fresh weight. Data obtained were analyzed using analysis of variance (ANOVA) and post hoc Honestly Significant Difference (HSD) test at significance levels of 5% and 1%. The results indicated a significant effect of fermented goat manure fertilizer on the growth and yield of Holy Basil. The treatment with fermented goat manure fertilizer exhibited the best performance, resulting in a plant height of 33.45 cm, 36 leaves, leaf area of 6.73 cm2, and fresh weight of 42.18 g. In contrast, the treatment without fertilizer and with goat manure fertilizer achieved lower measurements, with plant heights of 22.20 cm and 28.48 cm, leaf counts of 22 and 29, leaf areas of 3.43 cm2 and 4.57 cm2, and fresh weights of 16.60 g and 25.36 g, respectively. These findings highlight the potential of fermented goat manure fertilizer as a sustainable agricultural approach for optimizing Holy Basil growth and yield. Highlights: Fermented goat manure: Organic fertilizer produced through fermentation. Holy Basil: Medicinal and culinary herb with diverse applications. Sustainable agriculture: Promoting environmentally friendly farming practices. Keywords: Fermented goat manure, Holy Basil, Growth, Yield, Sustainable agriculture.